1984
DOI: 10.1002/ar.1092100207
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simulated increases in body weight for 30 and 60 days on bone robusticity of limb bones in rats

Abstract: The purpose of this study was to subject groups of weanling male rats each to a specific 10% simulated increase in body weight, ranging from 1.1G-2.0G, using constant centrifugation. (In this paper, "G" is the acceleration due to gravity.) After 30 and 60 days, rats were killed and perfused with 10% buffered neutral formalin (B.N.F.). The humerus, radius, ulna, femur, and tibia were removed, cleared of all soft tissues, weighed, and the total length measured. Bone robusticity was calculated using the ponderal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…After 60 days of centrifugation, a n inverse relationship was revealed for limb bone length and simulated increases in body weight. An investigation (Simon et al, 1984d) of changes in bone robusticity in male weanling rats revealed that, after 60 days of centrifugation, there was no set pattern to describe the relationship between simulated increases in body weight and bone robusticity for the male weanling rats. For radius and ulna, there were no significant (P > .05) differences in ponderal indices among the controls and experimental groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 60 days of centrifugation, a n inverse relationship was revealed for limb bone length and simulated increases in body weight. An investigation (Simon et al, 1984d) of changes in bone robusticity in male weanling rats revealed that, after 60 days of centrifugation, there was no set pattern to describe the relationship between simulated increases in body weight and bone robusticity for the male weanling rats. For radius and ulna, there were no significant (P > .05) differences in ponderal indices among the controls and experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…There were one female and its litter per centrifuge cage, af- fording two litters per experimental group. A period of acclimation to centrifugation was initiated, as described in Simon et al (1984d). Two females and their litters served as controls.…”
Section: The Animalsmentioning
confidence: 99%